PENGARUH PAPARAN MEDIA, SIKAP DAN NIAT TERHADAP PERILAKU TIDAK MEROKOK REMAJA DI YOGYAKARTA - Riyadi, Sujono (MEDIA ILMU KESEHATAN, 2020)
Background: Information about cigarettes lately is getting more intense. many teenagers who initially did not smoke became smokers because of the many cigarette advertisements seen and heard. Methods: Data obtained by distributing questionnaires, respondents as many as 400 adolescents and then analyzed the path using stata. Results: There is a direct influence on the intention of adolescents not to smoke towards non-smoking behavior of adolescents in the Kulon Progo Regency of Yogyakarta (b = 1.74; 95% CI = 1.18 to 2.29; p <0.001). Conclusion: Direct effect of the intention of adolescents not to smoke on adolescent non-smoking behavior. Indirect effect between media exposure and non-smoking attitudes on non-smoking behavior in Kulon Progo Regency, Yogyakarta.